Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có:
\(\frac{a}{b}=\frac{a\times\left(b+m\right)}{b\times\left(b+m\right)}=\frac{a\times b+a\times m}{b\times b+b\times m}\)
\(\frac{a+m}{b+m}=\frac{\left(a+m\right)\times b}{\left(b+m\right)\times b}=\frac{a\times b+m\times b}{b\times b+b\times m}\)
vì \(\frac{a}{b}>1\) nên \(a>b\), ta suy ra \(a\times m>b\times m\)
hay \(a\times b+a\times m>a\times b+m\times b\)
hay \(\frac{a\times b+a\times m}{b\times b+b\times m}>\frac{a\times b+m\times b}{b\times b+b\times m}\)
hay \(\frac{a}{b}>\frac{a+m}{b+m}\)
Vì \(\frac{a}{b}>1\)
=> a > b
=> a.m > b.m
=> a.m + a.b > b.m + a.b
=> a.(b + m) > b.(a + m)
=> \(\frac{a}{b}>\frac{a+m}{b+m}\)
Ta có:
x,26+2,y4+3,4a=x,00+0,2+0,06+2,04+0,y+3,4+0,0a
=(x,00+0,y+0,0a)+(2,04+0,2)+(3,4+0,06)
=x,ya+2,24+3,46
=x,ya+5,7<5,8
=>x,26+2,y4+3,4a<5,8
a) (-2)+ (-5) = -7
Vì: -7< -5
=> (-2)+ (-5) < -7
b) (-3)+ (-8)= -11
Vì: (-10) > (-11)
=> -10> (-3)+ (-8)
a, \(\left(-6\right)+\left(-3\right).....\left(-6\right)\)
\(\left(-9\right)< \left(-6\right)\)
Vậy \(\left(-6\right)+\left(-3\right)< \left(-6\right)\)
b,\(\left(-9\right)+\left(-12\right)....\left(-20\right)\)
\(\left(-21\right)< \left(-20\right)\)
\(\Rightarrow\left(-9\right)+\left(-12\right)< \left(-20\right)\)
\(a\)) \(3< 5\)
\(b\)) \(-3>-5\)
\(c\))\(4>-6\)
\(d\)) \(10>-10\)
a) Xét: \(1-\frac{3}{4}=\frac{1}{4}\); \(1-\frac{97}{98}=\frac{1}{98}\)
Vì \(\frac{1}{4}>\frac{1}{98}\) nên \(\frac{3}{4}< \frac{97}{98}\)
b) Xét: \(1-\frac{42}{43}=\frac{1}{43}\); \(1-\frac{112}{113}=\frac{1}{113}\)
Vì \(\frac{1}{43}>\frac{1}{113}\) nên \(\frac{42}{43}< \frac{112}{113}\)
Ta có: (-6) + (-3) = -(6 + 3) = - 9
nên: (-6) + (-3) < (-6)